Fitting as a temporal sensemaking process: Shifting trajectories and stable themes. (July 2019) - Jansen, Karen J; Shipp, Abbie J
This study identifies several mechanisms and the overall process by which individuals understand their evolving fit with their work environment. Prior person‒environment research has emphasized one-time quantitative assessments of fit, primarily as new entrants enter their work environment. In this study, we employed a qualitative approach to investigate the following question: how do long-tenured professionals make sense of fit over time? Three key findings emerged from the fit-related histories we collected. First, we discovered four prototypical fit trajectories, which were constructed from temporal comparisons with past, present and future fit, and employed to make momentary sense of events occurring in the work environment. Second, we identified two fit processes that played out over time: a slow accumulation journey and a sudden identity-threat journey. Third, we found that individuals' set of fit experiences was explained by one of four enduring fit themes, explaining their pattern of fit experiences over time and their reaction to misfit. Most surprising was the significant turnover among our long-tenured participants in the year or so following our interviews. Our findings break from traditional thinking about fit as predicting outcomes in the moment, to fitting as both a journey and a retrospective and prospective process of sensemaking.